Neuropilin-2 and its transcript variants correlate with clinical outcome in bladder cancer - Förster, Sarah; Givehchi, Maryam; Nitschke, Katja; Mayr, Thomas; Kilian, Kerstin; Dutta, Samikshan; Datta, Kaustubh; Nuhn, Philipp; Popovic, Zoran V.; Muders, Michael H.; Erben, Philipp (Genes, 2021)
Urothelial bladder cancer ranks among the 10 most frequently diagnosed cancers worldwide. In our previous study, the transmembrane protein neuropilin-2 (NRP2) emerged as a predictive marker in patients with bladder cancer. NRP2 consists of several splice variants; the most abundant of these, NRP2a and NRP2b, are reported to have different biological functions in lung cancer progression. For other cancer types, there are no published data on the role of these transcript variants in cancer progression and the clinical outcome. Here, we correlate NRP2 and its two most abundant transcript variants, NRP2A and NRP2B, with the clinical outcome using available genomic data with subsequent validation in our own cohort of patients with muscle-invasive bladder cancer. In addition to NRP2, NRP1 and the NRP ligands PDGFC and PDGFD were studied. Only NRP2A emerged as an independent prognostic marker for shorter cancer-specific survival in muscle-invasive bladder cancer in our cohort of 102 patients who underwent radical cystectomy between 2008 and 2014 with a median follow-up time of 82 months. Additionally, we demonstrate that high messenger expression of NRP2, NRP1, PDGFC and PDGFD associates with a more aggressive disease (i.e., a high T stage, positive lymph node status and reduced survival).
Gesehen am 14.07.2021